Panduratin A Inhibits TNF Alpha-Stimulated Endothelial Cell Activation Through Suppressing the NF-κB Pathway - Kriangkrai Kiatsoonthon; Nitchakarn Phimthong; Saranyapin Potikanond; Nitwara Wikan; Wutigri Nimlamool (Biomolecules)
Upon exposure to inflammatory stimuli including TNF-α, endothelial cells are activated leading to the adhesion of monocytes to their surface. These events are involved in the pathophysiology of atherosclerosis. Since TNF-α activates the NF-κB pathway, which contributes to atherosclerosis, targeting this signaling pathway may help prevent the risk of developing the disease. The current study elucidated the inhibitory effect of panduratin A (PA) on TNF-α-induced endothelial activation and monocyte adhesion. We discovered that PA reduced the level of pro-inflammatory cytokine IL-6 and chemokine MCP-1 in the media collected from endothelial cells stimulated with TNF-α. In addition, PA inhibited the expression of ICAM-1 and VCAM-1 on the surface of TNF-α-induced endothelial cells resulting in a decrease in the number of monocytes attached to endothelial cell surface. Mechanistically, PA prevented IκB degradation and specifically suppressed NF-κB phosphorylation and nuclear translocation in endothelial cells. However, PA had no inhibitory effect on the phosphorylation of AKT, ERK1/2, p38, and JNK. Taken together, PA blocked the production of cytokine and chemokine, adhesion molecules, and monocyte adhesion in response to TNF-α stimulation, in part, through NF-κB inhibition. Our study suggests that PA may possibly be effective in blocking the pathophysiology of atherosclerosis.